Impact of development of National Agriculture Market (e-NAM) on farmers - SWAIN, PRASANTA KUMAR; JAMIR, CHUBAMENLA; DINERSTIEN, MICHAEL; NARULA, SAPNA (The Indian Journal of Agricultural Sciences, 2022)
In developing countries like India, a well-functioning agricultural sector is crucial for economic growth and livable incomes. In an agricultural market system, prices can organize production efficiently by encouraging farmers to serve markets with excess demand and provide the levels of quality and varieties that consumers prefer. Though the state often plays a large role in market organization, the Government of India has been pressing for market reforms with State Governments to deal with market inefficiencies. One such major move has been to promote integrated markets across space and time in the country through the adoption of the National Agriculture Market Scheme (e-NAM). This paper examines the impact of the adoption of e-trading through e-NAM in regulated stand-alone wholesale APMC markets in Rajasthan on price realization by farmers in select commodities and its impact on market arrivals as a measure of market development. Difference-in-difference estimates indicate increase in farmers’ prices or quantities, consistent with increased demand and supply, while survey evidence suggests areas for further efficiency gains. The survey was conducted in select e-NAM APMC markets in Rajasthan during March–May 2021 and 2022.